2009
DOI: 10.1097/rlu.0b013e3181b7d95c
|View full text |Cite
|
Sign up to set email alerts
|

F-18 FDG-PET/CT Evaluation of Patients With Differentiated Thyroid Cancer With Negative I-131 Total Body Scan and High Thyroglobulin Level

Abstract: Our results indicate that F-18 FDG-PET/CT is a useful diagnostic tool in patients with differentiated thyroid carcinoma and with negative I-131 total body scans and high Tg levels. The levothyroxine therapy regimen does not influence F-18 FDG-PET/CT results and the rate of F-18 FDG-PET/CT positive results appears to correlate with the Tg levels. The highest accuracy is reached when the study is performed for patients with Tg levels higher than 21 ng/mL.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
45
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 65 publications
(49 citation statements)
references
References 39 publications
3
45
1
Order By: Relevance
“…In the context of known non-iodine-avid oligometastases, the detection of additional sites of disease is a pivotal issue in the decision-making process regarding resection. 18 F-FDG PET has been shown to be an effective tool for detecting thyroid cancer recurrence or metastases [8][9][10][11][12][13][14][15][16][17]. A recent meta-analysis of 17 studies between 1990 and 2008 including a total of 571 patients found an overall sensitivity for PET of 0.835 (95% CI 0.791-0.873) and specificity of 0.843 (95% CI 0.791-0.886) [22].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In the context of known non-iodine-avid oligometastases, the detection of additional sites of disease is a pivotal issue in the decision-making process regarding resection. 18 F-FDG PET has been shown to be an effective tool for detecting thyroid cancer recurrence or metastases [8][9][10][11][12][13][14][15][16][17]. A recent meta-analysis of 17 studies between 1990 and 2008 including a total of 571 patients found an overall sensitivity for PET of 0.835 (95% CI 0.791-0.873) and specificity of 0.843 (95% CI 0.791-0.886) [22].…”
Section: Discussionmentioning
confidence: 99%
“…In order to make an estimate of the accuracy of PET-CT we adopted a cut-off for defining a true-negative PET-CT scan as a negative scan and no rise in thyroglobulin over at least a 12-month period following the scan with no clinical or radiological evidence of disease. Although similar to the methodology of other series [8,11,13,17,25], this definition is limited by the often indolent nature of thyroid cancer, along with the ability of exogenous thyroid hormonemediated TSH suppression to limit disease progression. It is a common clinical experience that a low level of thyroglobulin may persist for many years without any evidence of progression and negative imaging; in this situation it is not possible to be dogmatic regarding the source of the thyroglobulin.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bertagna et al reported that F-18 FDG PET/CT positive results correlated with the serum thyroglobulin level in patients with negative I-131 whole body scan and high serum thyroglobulin level. They also reported that F-18 FDG PET/CT showed highest accuracy when the patient's thyroglobulin level was higher than 21 ng/mL (Bertagna et al, 2009). In addition to that, they also revealed that the levothyroxine therapy regimen does not influence F-18 FDG PET/CT results.…”
Section: F-18 Fluorodeoxyglucose Pet/ctmentioning
confidence: 99%
“…Furthermore there are reports on the use of 99mTc-MIBI imaging in post-surgical evaluation of thyroid cancer, for residual tumor localization, especially when the 131I-Na whole-body scan is negative with detectable values of thyroglobulin [2]. However, this indication has been almost completely replaced by 18F-FDG PET/CT imaging [3].Treglia and colleagues reported the results of 21 studies, accurately selected by rigorous methodology out of 690 articles. The 21 pooled studies included nearly two thousand patients.…”
mentioning
confidence: 99%